A 25‐year experience of endomyocardial biopsy safety in infants. Issue 5 (29th April 2013) - Zhorne, Derek; Petit, Christopher J.; Ing, Frank F.; Justino, Henri; Jefferies, John L.; Dreyer, William J.; Kearney, Debra; Crystal, Matthew A.
<x xml:space="preserve">Abstract</x> Objectives To analyze the outcomes and risk factors associated with endomyocardial biopsy (EMB) in children less than one year of age. Background EMB has proven to be an integral diagnostic tool to evaluate suspected myocarditis, identify tumor histology, and provide tissue‐graft surveillance after cardiac transplantation. The morbidity and mortality of EMB has been well established in the adult literature and reviewed in the general pediatric population, but there remains limited data for children in the first year of life. Methods We retrospectively reviewed the cardiology database at our institution to identify patients less than one year of age who underwent EMB between 1984 and 2008. Cardiac catheterization reports were reviewed for patient demographics, biopsy indication, procedural details, and complications. Results A total of 99 EMBs were performed, 49 for evaluation of suspected myocarditis, 43 for transplant rejection surveillance, 3 to identify tumor histology, and 4 for suspected endocardial fibroelastosis. Forty procedures were performed in children age < 6 months with 11 complications and 59 procedures performed in children age ≥ 6 months with four complications. In total, there were 12 EMB procedures (12.1%) with associated complications: 9 arrhythmias, 4 perforations requiring pericardiocentesis, 1 pneumothorax, and 1 death. Univariate analysis revealed a significant association between perforation and both weight <8 kg (P = 0.05) and age <6 months (P = 0.01). Conclusion Endomyocardial biopsies can be performed safely in infants, although children under 6 months of age and less than 8 kg represent a high risk group and deserve special consideration due to the incidence of complications in this cohort.© 2013 Wiley Periodicals, Inc.